(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Zemlyanaya A.S. Keywords: implication, individual style, artistic perception, pragmatics, irony, linguistic device, stylistic device. The article deals with the notion of implicature as a text category and implication as a key component of Jane Austen’s individual style and artistic perception. For the analysis of the implicature pragmatics, materialized in the text through linguistic integument, it is essential to designate language characteristic qualities of the text. Irony is presented as a dominant linguistic device in Jane Austen’s work, marked by implicature and pragmatics. Linguistic and stylistic devices of different language levels are studied in the article as the representation of the author’s individual manner of speech from the point of view of implication pragmatics of the author’s individual style.